PENGARUH DANA PIHAK KETIGA, LIKUIDITAS DAN RISIKO PASAR TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Studi Kasus Pada Bank Mandiri, BRI, BNI dan BTN Periode 2015-2019) - Rr.Dimas Veronica Priharti; Marisa Rizki; Tati Herlina (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
The purpose of this study is to determine the influence of third party funds, liquidity and market risk on the profitability of banking companies listed on the IDX (case studies on Mandiri Bank, BRI, BNI and BTN for the 2015-2019 period). The analytical method used in this study is multiple linear regression with a significance level of 5 percent. In addition, this study also carries out classical assumption tests which included normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The type of data used is secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). From the results of tests conducted on this study, it is known that simultaneously Third Party Funds (TPF), Liquidity (LDR) and Risk Market (NIM) on Profitability (ROA) in State-Owned Banks for the 2015-2019 period, while the partial test results obtained that TPF had no significant influence, LDR had no significant influence and NIM had a significant influence. The results of the analysis of the coefficient of determination adjusted R Square is 0.719 or 71.9 percent, it shows that the percentage contribution of the influence of the variables of Third Party Funds (X1), Liquidity (X2) and Market Risk (X3) to the fluctuations in profitability (Y) is 71.9 percent while the remaining 20.9 percent is influenced by other variables not examined in this study.